ANALISIS RASIO LIKUIDITAS DAN RASIO RENTABILITAS UNTUK MENILAI KINERJA KEUANGAN PADA PT.UNILEVER INDONESIA TBK - Sri Mardiana (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
PT. Unilever Indonesia Tbk. also generally have the goal of gaining profit / profit, increasing the value of the company and others. However, in this case, based on financial statement data taken from PT. Unilever Indonesia Tbk. that the company experienced a decrease in the level of profit achievement, an increase in operating costs, the existence of assets or funds that were idle because they had not been used optimally. Data analysis techniques using ratio analysis such as liquidity ratios, current ratios, quick ratios and cash ratios The company's liquidity ratio has increased and decreased. The highest Current Ratio value occurred in 2016 at 71.5%, while the lowest value occurred in 2019 at 60.6%, or decreased by 10.9% from the highest. The highest Quick Ratio value occurred in 2015 at 29.9%, while the lowest value occurred in 2019 at 21.2%, or down 8.7% from the highest. The highest Cash Ratio value occurred in 2017 at 96.9%, while the lowest was in 2015 at 33.4%, or down 63.5% from the highest. The company's profitability ratio has increased and decreased. Through analysis tools, namely the profitability ratio of the company's financial performance is quite good because the Gross Profit Margin, Return On Assets and Return On Equity the company's performance is above the industry standard where the industry standard for gross profit margin is 30%, return on assets is 30%, and return on equity. 40% of the industry standard even though the Net Profit Margin is still below the industry standard of 20%.